America behind bars : trends in imprisonment, 1950 to 2000 - Ruddell, Rick, 1961- (Criminal justice (LFB Scholarly Publishing LLC), 2004)
Ruddell examines the political, cultural, and social factors that contributed to the growth in incarceration in the United States from 1952 to 2000. Controlling for the influences of economic stress, violent crime, unemployment, direct outlays for assistance, the percentage of population that is black, and the percentage of males aged 15 to 29 years, Ruddell studies the influences of political disaffection, civic disengagement, and social disruption on adult imprisonment trends. The findings provide evidence of the relationships between increases in the use of punishment and cultural or political values. The results also support the proposition that the use of punishment is an inherently complex and political process.